(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Background: The Basic Course Workshop in Medical Education Technologies (BCW), initiated by the National Medical Commission (NMC) in 2009, has become an integral part of faculty development programs. Objectives: In this context, this study aimed to evaluate faculty perceptions of their immediate and sustained knowledge and utilization of teaching, learning, and assessment methods, as well as the usefulness of medical educational technology workshops based on the revised basic course proposed by the National Medical Commission (India). Methodology: A dedicated four-day workshop was held for registered faculties of AIIMS, Rajkot, with limited participation (24 participants) to ensure effective hands on training. Post-workshop, anonymous retro-pre feedback forms containing both closed-ended and open ended questions were collected.